Six weeks of N-acetylcysteine antioxidant in drinking water decreases pathological fiber branching in MDX mouse dystrophic fast-twitch skeletal muscle - Redwan, Asma; Kiriaev, Leonit; Kueh, Sindy; Morley, John W.; Houweling, Peter; Perry, Ben D.; Head, Stewart I. (Frontiers in Physiology, 2023)
It has been proposed that an increased susceptivity to oxidative stress triggered by the absence of the protein dystrophin from the inner surface of the sarcolemma is a trigger of skeletal muscle necrosis in the dystrophin deficient muscular dystrophies. Here we use the mdx mouse model of human Duchenne Muscular Dystrophy to test the hypothesis that adding the antioxidant NAC to drinking water will ameliorate muscle fiber branching pathology, increased dystrophic muscle mass and susceptibility to eccentric contraction damage in mdx mouse fast-twitch EDL muscle. During the six-week treatment phase NAC reduced body weight gain in three- to nine-week-old mdx and littermate control mice without effecting fluid intake. Post-treatment EDL muscles were dissected out and attached to a force transducer to measure contractile properties and susceptibility to force loss from eccentric contractions after which EDL mass was recorded. To assess the degree of pathological fiber branching present in mdx EDL muscles single fibers were enzymatically dispersed. NAC significantly reduced muscle mass and abnormal fiber branching in the mdx EDL. In littermate control and mdx NAC did not alter susceptibility to eccentric contraction force loss. We hypothesize chronic NAC treatment reduces muscle mass by slowing the degenerative cycles and reducing the number of complexed branched fiber reported to be responsible for the dystrophic hypertrophy.